Pengaruh Audit Tenure, Audit Fee, Ukuran Perusahaan, Reputasi KAP, dan Komite Audit terhadap Kualitas Audit - Angelina Zahra Ramadhaneiva; Eko Wahjudi (Commodities, Journal of Economic and Business, 2026)
The development of the business world encourages companies to improve audit quality in order to produce reliable and trustworthy financial statements. This study aims to analyze the effect of audit tenure, audit fee, firm size, public accounting firm (KAP) reputation, and audit committee on audit quality in telecommunication companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study uses a quantitative approach with a causal associative research design. The sample was determined using a purposive sampling technique, resulting in 13 companies with a total of 65 observations. The dependent variable is audit quality, which is proxied by discretionary accruals using the Modified Jones Model. The independent variables include audit tenure, audit fee, firm size, KAP reputation, and audit committee. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that audit fee has a significant negative effect on discretionary accruals, which indicates a positive effect on audit quality. Firm size also has a significant effect on audit quality. Meanwhile, audit tenure, KAP reputation, and audit committee do not have a significant effect on audit quality. Simultaneously, all independent variables have a significant effect on audit quality.